Dynamic Agency and the q Theory of Investment - DEMARZO, PETER M.; FISHMAN, MICHAEL J.; HE, ZHIGUO; WANG, NENG (Journal of Finance, 2012)
We introduce dynamic agency into the neoclassical q theory of investment. Costly external financing arises endogenously from dynamic agency, and influences firm value and investment. Agency conflicts drive a history-dependent wedge between average q and marginal q, and make the firm’s investment policy dependent on realized profits. A larger realized profit induces higher investment, and hence a larger firm. Investment is relatively insensitive to average q when the firm is “financially constrained ”(i.e. has low financial slack). Conversely, investment is sensitive to average q when the firm is relatively “financially unconstrained,” (i.e. has high financial slack). Moreover, the agent’s optimal compensation is in the form of future claims on the firm’s cash flows when the firm’s past profits are relatively low and the firm has less financial slack, whereas cash compensation is preferred when the firm has been profitable, agency concerns are less severe, and the firm is growing rapidly. To study the effect of serial correlation of productivity shocks on investment and firm dynamics, we extend our model to allow the firm’s output price to be stochastic. We show that, in contrast to static agency models, the agent’s compensation in the optimal dynamic contract will depend not only on the firm’s past performance, but also on output prices, even though they are beyond the agent’s control. This dependence of the agent’s compensation on exogenous output prices (for incentive reasons) further feeds back on the firm’s investment, and provides a channel to amplify and propagate the response of investment to output price shocks via dynamic agency.